Mano-Impedancemetric Diagnosis of Esophageal Function in Children With Dyspepsia - Marina Ju. Stepanyan; Elena V. Komarova; Maksim M. Lohmatov (Union of pediatricians of Russia, 2018)
Background. Introduction of new methods of diagnosing functional disorders of the upper gastrointestinal tract into children's practice will reveal the true cause of changes in esophageal motility in its various pathologies, which will significantly change the treatment tactics, since the selection of therapy will be based on the pathogenetic mechanisms of disease development.Our aim was to highlight the capabilities and benefits of high-resolution mano-impedancemetry in comparison with esophagogastroduodenoscopy, which has been studied and used in pediatric practice for a long time, and to prove that only due to a new method for diagnosing esophageal motility disorders, it is possible to determine the cause of dyspeptic complaints in children.Patients and Methods. The results of our own examination of children aged from 7 to 17 years 11 months (n = 23) with clinical manifestations of functional disorders of the upper gastrointestinal tract have been presented.Results. According to the mano-impedancemetry data, it has been found that the time of the substrate in the esophagus (p<0.02) and the speed of its passage through the esophagus depend on the pressure in the distal esophagus: the lower the pressure in the distal esophagus, the lower the fluid flow rate and the higher the degree of its reflux (р<0.001). Decreased speed indicates hypotonia of the lower esophagus and lower esophageal sphincter, which provides only a correction by physiotherapeutic treatment methods since surgical intervention in such conditions is ineffective.Conclusion. The method of mano-impedancemetry allows to determine the indications for surgical treatment and to predict the efficacy of the conducted anti-reflux surgical correction.